2018
DOI: 10.1111/jfpe.12977
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat‐treated liquid whole egg on cake batter rheology and the quality of baked cake

Abstract: The aim of the present study is to investigate the effects of heat-treated liquid whole egg (LWE) on cake batter rheology (shear rate-viscosity and shear rate-shear stress) and quality characteristics (moisture loss, color, porosity, texture, and specific volume) of baked cakes. LWE was pasteurized at different levels which were 60-68 C for 2 and 5 min. Cake batter and baked cakes were prepared using both untreated and treated LWE, and rheological properties and quality characteristics were measured, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…Pseudo‐plastic behavior, which presents a decrease in apparent viscosity depending on the increase in shear rate, was observed from all cream formulations as can be seen in Figure (Song, Kim, & Chang, ). Although all cream formulations did not contain flour as an ingredient, the flow behaviors of all cream formulations (pseudo‐plastic behavior, n < 1) were consistent with the results given in previous researches (Arozarena, Bertholo, Empis, Bunger, & Sousa, ; Baixauli, Sanz, Salvador, & Fiszman, ; Latha, Bhat, & Bhattacharya, ; Ronda, Oliete, Gómez, Caballero, & Pando, ; Turabi et al, ; Uysal et al, ).…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Pseudo‐plastic behavior, which presents a decrease in apparent viscosity depending on the increase in shear rate, was observed from all cream formulations as can be seen in Figure (Song, Kim, & Chang, ). Although all cream formulations did not contain flour as an ingredient, the flow behaviors of all cream formulations (pseudo‐plastic behavior, n < 1) were consistent with the results given in previous researches (Arozarena, Bertholo, Empis, Bunger, & Sousa, ; Baixauli, Sanz, Salvador, & Fiszman, ; Latha, Bhat, & Bhattacharya, ; Ronda, Oliete, Gómez, Caballero, & Pando, ; Turabi et al, ; Uysal et al, ).…”
Section: Resultssupporting
confidence: 89%
“…An overall increase from 0.54 to 0.76 was observed in n value as the applied pasteurization parameters were increased. In another study, a significant change was obtained between the flow behavior indexes ( n , from 0.59 to 0.52) of cake batters (containing untreated and heat‐treated LWE) (Uysal et al, ). Ma et al () reported that heat treatment caused an increase in apparent viscosities of frozen egg white (from 0.43 to 0.52) and frozen egg yolk (from 6.94 to 10.38).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations